Construction site layout planning using multi-objective artificial bee colony algorithm with Levy flights - Yahya, M.; Saka, M.P. (Automation in construction, 2014)
Construction site layout planning has been recognized as a critical step in construction planning. The basic function of this process is to find the best arrangement of the temporary facilities according to multiple objectives that may conflict with each other and subjected to logical and resource constraints. The formulation of the construction site layout planning problem as an optimization problem turns out to be a nonlinear programming problem where there are conflicting multi-objectives to be achieved. It is shown that the swarm intelligence based meta-heuristic algorithms are quite powerful in obtaining the solution of such hard to solve type of optimization problems. In this study a multi objective artificial bee colony (MOABC) via Levy flights algorithm is proposed to determine the optimum construction site layout. The model is intended to optimize the dynamic layout of unequal-area under two objective functions. The performance of MOABC with Levy flights is demonstrated on a real benchmark construction engineering of construction site layout planning problem and the optimum solution obtained is compared with the one determined by the ant colony algorithm. •We propose MOABC via Levy flights to solve the optimum construction site layout.•The mode considers the CSLP problem as a continuous search problem.•Using Levy flight by employed bees has improved the efficiency of MOABC.•The model is applied to a practical case and proved to be robust and efficient.